Influencia Familiar en el Bajo Rendimiento Escolar en Estudiantes de cuarto grado, en la Unidad Educativa “José Ángel Palacio” Ciudad-Loja, periodo 2023-2024 - Conza Ramírez, Deysi Mireya (2024)
This research work, titled Family Influence on Low Academic Performance in Fourth Grade Students at José Ángel Palacio Elementary School, Loja City, Academic Period 2023- 2024, demonstrates how family dynamics influence students and impact their academic performance. The general objective is to analyze the family's influence and its repercussions on students' academic performance. The employed methodology is qualitative, descriptive, and non-experimental. Techniques used included interviews and direct observation, with instruments such as interview guides and observation sheets, validated by a panel of three experts. Data triangulation methodology was implemented to analyze the results. A non- probabilistic intentional sampling was conducted, focusing on teachers and students with low academic performance. The results reveal that students from dysfunctional families, who constantly experience conflicts, have poor communication, and lack affection and emotional support. As a result, these issues are reflected in low academic performance, inappropriate behavior, and difficulties in assuming school responsibilities. Additionally, other personal and socioeconomic factors influencing academic performance were identified, such as motivation, cognitive skills, health status, and learning styles. The research concludes that the family is the primary influence that positively affects students, but when there is family dysfunction, it negatively impacts students' academic performance, affecting their emotional well-being and learning capacity.